GlmS mediated knock-down of a phospholipase expedite alternate pathway to generate phosphocholine required for phosphatidylcholine synthesis in Plasmodium falciparum. Issue 18 (30th September 2021) - Sheokand, Pradeep Kumar; Narwal, Monika; Thakur, Vandana; Mohmmed, Asif
Abstract : Phospholipid synthesis is crucial for membrane proliferation in malaria parasites during the entire cycle in the host cell. The major phospholipid of parasite membranes, phosphatidylcholine (PC), is mainly synthesized through the Kennedy pathway. The phosphocholine required for this synthetic pathway is generated by phosphorylation of choline derived from the catabolism of the lyso-phosphatidylcholine (LPC) scavenged from the host milieu. Here we have characterized a Plasmodium falciparum lysophospholipase ( Pf LPL20) which showed enzymatic activity on LPC substrate to generate choline. Using GFP- targeting approach, Pf LPL20 was localized in vesicular structures associated with the neutral lipid storage bodies present juxtaposed to the food-vacuole. The C-terminal tagged glmS mediated inducible knock-down of Pf LPL20 caused transient hindrance in the parasite development, however, the parasites were able to multiply efficiently, suggesting that Pf LPL20 is not essential for the parasite. However, in Pf LPL20 depleted parasites, transcript levels of enzyme of SDPM pathway (Serine Decarboxylase-Phosphoethanolamine Methyltransferase) were altered along with up-regulation of phosphocholine and SAM levels; these results show up-regulation of alternate pathway to generate the phosphocholine required for PC synthesis through the Kennedy pathway. Our study highlights the presence of alternate pathways for lipid homeostasis/membrane-biogenesis in the parasite; these data could be useful to design future therapeutic approaches targeting phospholipid metabolism in the parasite.